Development of Higher Order Thinking Skills (HOTS) Test Instruments on Parabolic and Circular Motion Materials in High Schools - Muhammad Aizri Fadillah; Sahyar Sahyar (Berkala Ilmiah Pendidikan Fisika, 2023)
This research intends to produce HOTS test instruments on high school parabolic and circular motion materials. The Borg and Gall model of research and development (R&D) includes six stages: (1) preliminary investigation, (2) planning and equipment preparation, (3) expert initial product testing and revision, (4) limited field testing, (5) revision based on the results field testing, and (6) broader field test. The data analysis used was qualitative and quantitative. The HOTS test instrument consists of 20 multiple-choice questions, including ten on parabolic and circular motion. According to three experts from material, construction, and language, the outcomes of HOTS instrument validation showed valid and feasible to use with an average value of 0.95 (high validity). The characteristics of HOTS questions have met the criteria of validity as many as 18 questions, high reliability with a value of 0.71, nine questions with a medium difficulty level, an average differentiating power of 0.41 with a good category, and 17 questions have the effectiveness of effective deception. This research concluded that HOTS-based parabolic and circular motion instruments are feasible. Thus, the instrument can be used as training material and assessment of students’ HOTS in high schools.